1996
DOI: 10.1097/00003246-199603000-00004
|View full text |Cite
|
Sign up to set email alerts
|

A genomic polymorphism within the tumor necrosis factor locus influences plasma tumor necrosis factor-alpha concentrations and outcome of patients with severe sepsis

Abstract: The bi-allelic Ncol polymorphism within the TNF locus is a genomic marker for patients with increased TNF-alpha response and poor prognosis in severe sepsis. The amount of TNF released in situations of severe infection and sepsis appears to be influenced genetically. TNFB2 homozygous individuals displaying increased circulating TNF plasma concentrations combined with high mortality rate may be included in future studies testing anti-TNF strategies in severe sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
266
6
13

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 532 publications
(303 citation statements)
references
References 9 publications
18
266
6
13
Order By: Relevance
“…However, we found no association between alleles of either the TNF À308 or LTA þ 252 polymorphisms and disease outcome or severity. This contrasts with studies linking severe sepsis outcome and LTA þ 252 genotype, 36,37 and the TNF À308 polymorphism with outcome in septic shock and meningococcal disease. 39,40 However, our findings concur with those of another study in which it was reported that there is no association between the TNF À308 polymorphism and severe sepsis.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, we found no association between alleles of either the TNF À308 or LTA þ 252 polymorphisms and disease outcome or severity. This contrasts with studies linking severe sepsis outcome and LTA þ 252 genotype, 36,37 and the TNF À308 polymorphism with outcome in septic shock and meningococcal disease. 39,40 However, our findings concur with those of another study in which it was reported that there is no association between the TNF À308 polymorphism and severe sepsis.…”
Section: Discussionmentioning
confidence: 82%
“…Both the TNF À308 and LTA þ 252 polymorphisms have been associated with variations in TNF-a levels, [36][37][38] and may therefore have an effect on IMD severity and outcome. However, we found no association between alleles of either the TNF À308 or LTA þ 252 polymorphisms and disease outcome or severity.…”
Section: Discussionmentioning
confidence: 99%
“…The NcoI polymorphism in the tumour necrosis factor locus was significantly associated with mortality 36 and the polymorphism in the interleukin-1 receptor antagonist was associated with the incidence of severe sepsis. 37 The further identification of such risk alleles associated with increased probability of sepsis development is especially of interest for the clarification of pathomechanisms of sepsis including important pathways of receptor acti-vation and could be important for stratification of therapy.…”
mentioning
confidence: 99%
“…Also the interaction among various polymorphisms of anti/pro-inflammatory cytokines, such as IL-10 and TNF-a, helped in the identification of IL-10-1082GG/TNF-a -308 GG genotype interaction as relevant for the longevity rather than the single polymorphism of IL-10 or TNF-a [89]. The same conclusion as high risk factor for mortality due to sepsis and infections has been reported when HSP70-2A and TNF-b2 genotypes are associated [141]. All these findings therefore highlight the importance of knowing all the polymorphisms relevant to the inflammatory response in individuals rather than interpreting a polymorphism in isolation.…”
Section: Zinc-hsp70 Gene Interactionmentioning
confidence: 67%
“…Studies performed in children with meningococcal disease [112], in patients with septic shock [100,141], in old septic shock patients [143], and more recently in old patients affected by severe bronchus-alveolar infections [33], show that the TNF-a -308A allele (A+ carrier) is associated with adverse outcome with respect to TNF-a -308A allele (A-carrier). Moreover, patients with A+ carrier have less responsiveness to drugs and significantly increased risk of death [120].…”
Section: Zinc-tnf-a Gene Interactionsmentioning
confidence: 99%